Sistem Kontrol Engraving Acrylic CNC 3 Axis Berbasis Pc Menggunakan Arduino - pernandito, anderson _; Rahmawaty, Made; Tianur; Hendriko (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
CNC (Computer Numerical Control) machines have become an important part of various industries, including manufacturing and the arts. One of the important applications of CNC machines is engraving on acrylic materials, which are used to create high-quality detailed products. However, many 3-axis CNC machine control systems are expensive and complex, making them out of reach for many users. Therefore, this study aims to develop a more efficient and affordable 3-axis CNC acrylic engraving control system based on a PC using the Arduino. In previous studies, many studies have been carried out related to CNC machine control systems. Several studies have focused on developing PID control to improve the accuracy of CNC machine movements, while other studies have attempted to integrate the Arduino platform as the brain of a more effective control system. However, the research does not fully focus on the use of acrylic materials and does not provide integration with PCs as a user interface. The design of this system begins with selecting the right electronic components for the control system, including the Arduino as the main microcontroller, motor drive and the necessary sensors. In addition, the application's notebook-based user interface is designed to allow users to enter designs for direct engraving into the system. The use of PID control is optimized to ensure precise and precise CNC machine movement. This research produces a 3-axis acrylic CNC engraving machine control system on a PC using an Arduino. This system can control the movement of the CNC machine in three dimensions (X, Y and Z) with high precision. The application's user interface allows users to easily import designs for engraving. The final result data is the quality construction of the acrylic material, including the level of precision and detail engraved by the CNC machine.